Price Formation and Liquidity Provision in Short-Term Fixed Income Markets - D'Souza, Christopher; Lo, Ingrid; Sapp, Stephen (Bank of Canada, 2007)
Differences in market structures may affect the manner in which fundamental information is incorporated into prices. High levels of quote and trade transparency plus substantial quoting obligations in European government securities markets ensure that prices are informationally efficient. The relationship between price changes, order flow, relative depth and spreads across European and Canadian short-term government bond markets is examined via a reduced-form vector autoregression model. In European markets, dealers are able to quickly absorb private information elsewhere in the market. Consequently, spreads and the relative depth on the bid and offer sides of the market are found to be only slightly informative. Similarly, order flow, which reflects inventory management practices in addition to private information, explains a smaller proportion of the variation in asset returns in European markets than in Canadian interdealer brokered markets where no quoting obligations exist.

Les différences de structure de marché peuvent influer sur la manière dont l'information fondamentale est intégrée aux prix. Le degré élevé de transparence en amont et en aval des transactions et les rigoureuses obligations de cotation sur les marchés européens de titres d'État assurent l'efficience informationnelle des prix. À l'aide d'un modèle vectoriel autorégressif de forme réduite, les auteurs analysent la relation entre les variations de prix, le flux d'ordres, les écarts acheteur-vendeur et la différence de profondeur entre les deux côtés du carnet sur les marchés européens et canadiens des obligations d'État à court terme. Sur les marchés européens, les opérateurs peuvent assimiler rapidement l'information privée détenue par d'autres participants. Par conséquent, les écarts acheteur-vendeur et la différence de profondeur entre les deux côtés du carnet se révèlent peu informatifs. De même, le flux d'ordres, qui traduit aussi bien les pratiques de gestion des stocks que l'information privée, explique une proportion plus faible de la variation des rendements sur les marchés européens que sur le marché canadien du courtage intermédiaire, où il n'y a aucune obligation de cotation.